Proposal for improving the customer service process through digitization - Fukuhara Tengan, Alessandro (2024)
The problem posed in this investigation is that a mutual fund management company maintained traditional processes of subscription and redemption of quotas in the funds, which caused great economic inefficiencies and discontent among clients. That is why the objective of this research was to propose a proposal to improve customer service processes through the application of a digital transformation through agile methodologies such as Design Thinking and Lean Startup through quasi-experimental practical research. In this way, it was possible to increase profits and customer experience. After the implementation, it was evidenced that thanks to this, the number of AUMs and participants increased by +15% per month and +55%, since the implementation, respectively, translating, later, into higher profits for the company (+10%).